PROBLEMS OF EXPORT-IMPORT OPERATIONS ACCOUNTING IN UKRAINE'S EXTRACTION FIELD - Volkov, V.; Horoshkova, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article develops a systematic approach to the management of mining, using, export and import non-metallic minerals for construction considering the economic parameters of the development of the world market situation and the domestic market. The analysis showed that the classification of minerals used by the Public Service Geology and Mineral Resources of Ukraine, the State Statistics Committee of Ukraine and Statistics of foreign economic activity - codes UKTZED - do not coincide that complicates the study process using these official sources. According to the results of the conducted researches, the indicators of the dynamics of minerals production in their natural and costly dimensions have been found to be inadequate. An analysis of dynamics and geographic structure of export-import operations was also conducted with natural sand, pebbles, gravel and breakstone. The obtained results allowed us to conclude that the approach to formation of export minerals' flows is not rational, because it poses a threat to the financial state of the mining industry and the country. An analysis of the geographical structure of the export and import of natural sand, pebbles, gravel and breakstone allowed proposing the use of a systematic approach to rational extraction, the use of the country's mineral resources base, while taking into account export-import flows and the price conditions of the external and internal markets and taking into account the resource component of state security.
Keywords: mineral and raw materials base; nonmetallic minerals for construction; building stone; sand; expanded clay; forecasting; modeling; management